A cytotoxicity and comparative antibacterial study on the effect of Zataria multiflora Boiss, Trachyspermum copticum essential oils, and Enrofloxacin on Aeromonas hydrophila - Hassan Malekinejad; Behnaz Bazargani-Gilani; Amir Tukmechi; Hadi Ebrahimi (Mashhad University of Medical Sciences, 2012)
Objective: this study designed to test the antibacterial potency of enrofloxacin (ENR) and essential oils from Zataria multiflora Boiss (ZEO) and Trachyspermum copticum (TEO)on Aeromonas hydrophila. Material and Methods: The antibacterial potency of test compounds was determined by several methods including the inhibition zone diameter determination, microbroth dilution method and colorimetric method of MTT. The cytotoxicity of test substances was assessed on Chinook salmon (Oncorhynchus tshawytscha) embryo (CHSE-214) cells. Results: Results showed that ENR and tested essential oils exert antibacterial effect against A. hydrophila. Moreover, ENR exerted the most potent antibacterial effect with MIC values of 62.5 ng/ml. The natural compounds of ZEO and TEO also showed antibacterial effects with rather high MIC values of 0.315 mg/ml, and 1.25 mg/ml, respectively. None of the tested substances showed toxicity on CHSE-24 cells. Conclusion: It is concluded that ZEO and TEO could be applied to prevent from A. hydrophila infection. Moreover, data also suggest that MTT method could be both cost- and time-effective and accurate method of MIC determination.